2018
DOI: 10.1093/intqhc/mzy068
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality from adverse effects of medical treatment in the UK, 1990–2013: levels, trends, patterns and comparisons

Abstract: ObjectiveTo present an update on incidence and mortality from adverse effects (AEs) of medical treatment in the UK, its four countries and nine English regions between 1990 and 2013.DesignDescriptive epidemiological study on AEs of medical treatment. AEs are shown as a single cause-of-injury category from the Global Burden of Disease (GBD) 2013 study.Data sourcesThe GBD 2013 interactive data visualisation tools ‘Epi Visualisation’ and ‘GBD Compare’.Outcome measuresThe means of incidence and mortality rates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…4,5 It is commonly reported that the incidence of bladder cancer in men is much higher than that in women, which is strongly associated with CS. 6 There are more than 60 established carcinogens, which have been classified into five major groups: polycyclic aromatic hydrocarbons (PAH), nicotine-derived nitrosamines, azaarenes, miscellaneous organic compounds, and inorganic compounds. Various molecular mechanisms have been proposed for CSinduced carcinogenesis, but the underlying mechanisms of smoking leading to bladder cancer development are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It is commonly reported that the incidence of bladder cancer in men is much higher than that in women, which is strongly associated with CS. 6 There are more than 60 established carcinogens, which have been classified into five major groups: polycyclic aromatic hydrocarbons (PAH), nicotine-derived nitrosamines, azaarenes, miscellaneous organic compounds, and inorganic compounds. Various molecular mechanisms have been proposed for CSinduced carcinogenesis, but the underlying mechanisms of smoking leading to bladder cancer development are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence in this article refers to the number of new cases or individuals who experience an AEMT event during a particular time period. Estimation of incidence is carried out by taking the number of new cases in a year, which is then divided by the mid-year population of that country [12].…”
Section: Incidence (Per 100000)mentioning
confidence: 99%
“…However, limited data exist on the levels, trends and patterns of the causes and effects of AEMT globally and in each region as defined by WHO over a specific period. Earlier reports relating to patient safety and AEMT were primarily based on random reviews of selected medical records and hospitals during a specific time [11,12]. Therefore the present study aims to analyze global and region-specific patterns of incidence and mortality, and predict possible emerging trends due to AEMT using the GBD injuries and risk factor study for the period 1990-2017.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that a quarter of them are preventable. 10,13 A study published in 2019 shows an annual rate of death due to adverse events of medical treatment from 4180 in 1990, to 5180 in 2016 and in total during this period they were estimated 123,603 deaths for this cause. 17…”
Section: What Impact Does Error Have On Health Care?mentioning
confidence: 99%